Psikoseksualitas PascaHisterektomi: Perspektif Wanita Dalam Budaya Indonesia: Psychosexuality A Post-Hysterectomy: Women's Perspectives Within Indonesian Culture - Ridwan Sofian; Khafidhiyah Nur Insaniyah (Journal of Nursing Care and Biomolecular, 2025)
Background: In Indonesian culture, women who have undergone hysterectomy often perceive the loss of the uterus as a loss of femininity, which can diminish self-esteem and affect sexual life as well as interpersonal relationships. Objective: This study aims to explore the psychosexual experiences of women post-hysterectomy from an Indonesian cultural perspective. Method: A qualitative research approach was employed through in-depth interviews with six participants at RS Wava Husada Kepanjen. Results: Three main themes emerged: (1) When Sexual Relations Become a Physical Burden, where participants experienced pain and vaginal dryness during sexual intercourse. (2) When Love Loses Its Passion, where participants lost the desire for intimacy. (3) Shadows of Separation, where participants felt incapable of satisfying their husbands and feared abandonment. Conclusion: Hysterectomy has a significant impact on the physical, psychological, and relational aspects of women's lives, particularly concerning sexual relationships. Complaints such as pain and vaginal dryness disrupt sexual activity, reduce the frequency and quality of relationships, and create tension between partners. Further research is needed to understand the experiences of partners in addressing the psychosexual issues faced by women post-hysterectomy. Keywords: Post-hysterectomy, Psychosexual Issues, Women's Perspective